(untitled) (Federal University Gusau Faculty of Education Journal, 2026)
This position paper is an exposition of the practical relevance of Artificial Intelligent (AI) to the teaching and learning Mathematics, the bedrock of science, and a foundation knowledge for scientific development and economic growth of every nation. Mathematics is an academic discipline that embraces all courses, scientific models, critical thinking, creative thinking, problem-solving and development of Artificial Intelligent (AI). AI is transforming various fields of human endeavors, including health care, politics, economics, research and education. The rapid development of AI technology has become a need for mathematics educators, to enhancing teaching and learning of mathematics. Therefore, the concept of AI is examined along its benefits in teaching and learning of mathematics. The paper also explained some AI tools use in mathematics classroom, such as MathGPTPro, Wolfram Alpha, Julius AI, Maple calculator, etc. It then highlighted some constrictions in using AI tools in teaching and learning of mathematics. In conclusion, utilizing AI tools has a lot of benefits, as such mathematics educators, curriculum planners and stakeholders in the education industry must put their hands on desk to maximize the merits of AI in mathematics teaching-learning, while mitigating associated challenges. It is recommended that Educators and developers should collaborate to create AI powered resources that cater for diverse learning needs and styles, Teacher professional development programs should also be designed to support the effective integration of AI tools in mathematics education.